Impact of amlodipine on clinical outcomes for heart failure in patients with dilated cardiomyopathy: a Korean nationwide cohort study - Bae, SungA; Kim, Wan Kee; You, Seng Chan; Kim, Minkwan; Jung, In Hyun (Frontiers in Cardiovascular Medicine, 2023)
Amlodipine, widely used as a first-line treatment for hypertension, has inconclusive clinical evidence regarding its efficacy in patients with heart failure. This retrospective cohort study aimed to investigate the clinical effectiveness of amlodipine treatment after hospitalization for heart failure in patients with dilated cardiomyopathy (DCMP). A total of 20,851 patients who were diagnosed with DCMP and admitted for heart failure between 2005 and 2016 according to Korean nationwide medical insurance service database were enrolled. Amlodipine use was defined as its prescription at the time of discharge and for at least 180 days within a year. The primary outcome was all-cause death, and the secondary outcome was heart failure rehospitalization during a 5-year period. The outcomes between patients who received amlodipine (n=6,798) and those who did not (n=14,053) were compared. During the 5-year follow-up, the group treated with amlodipine exhibited a significantly lower risk of all-cause death and heart failure rehospitalization than the group not treated with amlodipine (all-cause death: adjusted hazard ratio [HR]: 0.64, 95% confidence interval [CI]: 0.59–0.70, p<0.001; cardiovascular death: adjusted HR: 0.71, 95% CI: 0.62–0.81, p<0.001; heart failure rehospitalization: adjusted HR: 0.92, 95% CI: 0.86–0.98, p=0.006). In a subgroup analysis, amlodipine had a significant impact on decreasing all-cause mortality in older adults, those with a higher systolic blood pressure, and those with a lower Charlson Comorbidity Index. In summary, amlodipine use after hospitalization for heart failure in patients with DCMP was associated with a lower risk of all-cause death and readmission for heart failure.